Disparities in the Induced Rain Attenuation between Beacon (Narrowband) and Broadband Satellite Links in Tropical Zones - Idrissa Abubakar; Jafri Din; Hong Yin Lam (Institute of Advanced Engineering and Science, 2018)
The utilisation of higher frequency bands above 10 GHz by the satellite industries to provide the bandwidth (BW) required for broadband multimedia services, video conferencing, direct-to-home TV programmes and IP data requires the understanding of atmospheric losses and good link planning for satellite-to-earth links. The trade-off between the service availability, data rate and BW determine the type of modulation scheme and error corrections to be employed. These services also depend on the link performance under adverse atmospheric conditions, especially rain-induced attenuation. In this research, study measurements were conducted on space-to-earth satellite links using the beacon narrowband and broadband IP carrier signals of a Nigcomsat-1R satellite operating at 42.5°E. A VSAT receiving terminal at a latitude of 7.4°N, longitude of 9.04°E and altitude of 334 m above sea level was utilised to quantify the rain-induced attenuation of both the beacon and broadband signals during rain events. The measurements were then compared with the link performance under clear sky conditions. The performance revealed that, when compared with the broadband signal, the induced rain attenuation on beacon signal presented a disparity in the responses, resulting in significant variations of 10.14 dB in the carrier-to-noise ratio (C/N) and 17.42 dB in the received signal level at a Ku-band frequency of 12.518 GHz. These observations were also compared with the Crane global rain map and ITU-R P.618-12. Both models disagreed with the measurement values for Abuja, Nigeria.